Quality evaluation of mince-based fish burger from tilapia (Oreochromis mossambicus) during frozen storage (Journal of the Bangladesh Agricultural University, 2020)
Biochemical, microbial and sensory qualities of burger patty and fish mince prepared from Mozambique tilapia were determined during frozen storage condition (-18 ºC) up to 75 days. Significant decrease (P>0.05) in moisture and lipid contents of mince and burger were observed during the storage period although moisture and lipid contents of burger was higher than the mince. Protein content of mince and burger reduced at the end of storage period however, reduction rate was not significant (p>0.05) and protein content of burger was slightly higher than that of mince. Ash content of both mince and burger increased significantly (p